Influence of Year, Parity and Birth Type on Milk Yield and Milk Components of Bandırma Sheep German Black Head Mutton x Kıvırcık - Tamer Sezenler; Ayhan Ceyhan; Deniz Soysal; Mesut Yıldırır; Seyrani Koncagül; Mehmet Akif Yüksel (Journal of Agricultural Sciences)
This study was conducted to investigate the effects of year, parity and birth type BT on lactation milk yield LMY , adjusted lactation milk yield based on 150 days lactation length LMY150 , lactation length LL , average daily milk yield ADMY and milk components MC of Bandırma sheep. The study was carried out with 54 ewes in 2011 and 70 ewes in 2012 under semi-intensive conditions. LMY, LMY150, LL and ADMY of Bandırma sheep were determined as 70.31 kg, 73.29 kg, 142.02 days and 488.19 g, respectively. The effect of the year on LL was significant P